Antinuclear antibodies positivity in women in reproductive age: From infertility to adverse obstetrical outcomes – A meta-analysis. (February 2023) - Ticconi, Carlo; Inversetti, Annalisa; Logruosso, Eleonora; Ghio, Matilda; Casadei, Luisa; Selmi, Carlo; Di Simone, Nicoletta
Abstract: This systematic review and meta-analysis were designed to identify possible correlations between isolated serum antinuclear antibody (ANA) and (i) infertility in the context of in-vitro fertilization (IVF), (ii) idiopathic recurrent pregnancy losses (RPL), and (iii) second/ third trimester pregnancy complications. We performed a systematic review and meta-analysis of the literature in PubMed Library database from inception to March 2022 following PRISMA guidelines. Our pooled results showed a lower pregnancy rate among ANA-positive women undergoing IVF/ICSI compared to ANA-negative women undergoing the same procedures (279/908 versus 1136/2347, random effect, odds ratio -OR- 0.50, 95% confidence interval -CI- 0.38–0.67, p 0.00001, I 2 = 58%). We also reported a higher miscarriage rate among ANA-positive compared to ANA-negative women (48/223 versus 109/999, random effect, OR: 3.25 95% CI: 1.57–6.76, p = 0.002, I 2 = 61%) and a lower implantation rate (320/1489 versus 1437/4205, random effect, OR: 0.51, 95% CI: 0.36–0.72, p = 0.0001, I 2 = 78%). Regarding RPL, pooled results demonstrated a higher prevalence of ANA-positivity in RPL women compared to controls (698/2947 versus 240/3145, random effect, OR: 3.22, 95% CI: 2.12–4.88, p 0.00001, I 2 77%), either using > 2 or > 3 pregnancy losses threshold for defining RPL. Heterogeneity of reporting outcome did not allow a quantitative analysis and led to no clear demonstration of an effect of serum ANA on the incidence of stillbirth, preeclampsia and hypertensive disorders. In conclusion, the unfavorable effect of serum ANA was observed in women following IVF. Similarly, ANA were associated with the risk of RPL, while data were unconclusive in terms of late pregnancy complications. Highlights: The obstetrical outcomes in ANA+ patients are still a matter of debate. Clinical pregnancy rate and implantation rate after in vitro fertilization was lower in ANA+ patients compared to controls Miscarriage rate after in vitro fertilization was higher in ANA+ compared to control women. An increased rate of recurrent pregnancy losses (RPL) was found in ANA+ pregnant women compared to controls. It was not possible to establish a clear effect of ANA on second and third trimester pregnancy complications.